Sodium silicate mediated response of antioxidative defense system in Lycopersicon esculentum mill. under water stress - Chanchal Malhotra; Riti Thapar Kapoor; Deepak Ganjewala; NB Singh (International Journal of Phytomedicine, 2017)
The present study was designed to study the effect of water stress on Lycopersicon esculentum Mill. and role of sodium silicate in the protection of tomato plants under water deficit condition. Different biochemical parameters such as photosynthetic pigments, protein, sugar, MDA content, proline, nitrate reductase activity and activities of antioxidant enzymes (SOD, CAT, APX and POX) were examined in tomato leaves at 40 and 60 DAS by the standard methods. The lycopene and β-carotene contentsin tomato fruits were also analyzed at 60, 65 and 70 DAS. Water stress significantly decreased relative water content (RWC), pigment content, sugar and protein contents in tomato leaves at 60 DAS but the accumulation of proline was stimulated in tomato leaves under water deficit condition. The activities of antioxidant enzymes such as SOD, CAT, APX and POX were significantly increased under (3d and 6d) water stress condition at 60 DAS. This study offers first hand information on the water stress-induced oxidative stress in Lycopersicon esculentumand development of antioxidative defense system against drought.The results obtained clearly indicated the positive impact of sodium silicate in protection of tomato plants under water deficit condition.